Mentality Readiness, Morality, and Work Ethic in the Industrial World: A Counseling Program at SMK Fatahillah 1 Cilegon - Tatang Mahpudin; Titis Sri Wulan; Silvia Rachmadani; Muhammad Rizki Ashari; Siti May Khofifa (Journal of Education Psychology and Social Development, 2026)
Mental, moral, and work ethic readiness are important foundations that Vocational High School (SMK) students must have in facing the demands of an increasingly competitive industrial world. These three aspects not only support technical skills, but also determine students' success in adapting to real work dynamics. A strong mentality helps students face the pressures and challenges of industry, good morality forms integrity and responsibility in work, while a strong work ethic encourages discipline, productivity, and professionalism. Based on this urgency, the community service team carried out counseling activities at SMK Fatahillah 1 Cilegon with the theme "Mentality, Morality, & Work Ethic Readiness in the Industrial World". This activity was carried out through interactive lectures and group discussions. The results of the implementation showed that students gained a deeper understanding of the importance of morality as a basis for forming a work ethic, as well as mental readiness in facing a competitive world of work. This counseling contributed to strengthening students' character to be more adaptive, competitive, and ready to face changes in the industrial era 4.0 towards 5.0. Thus, this activity is a strategic step in preparing vocational high school graduates who are not only technically proficient but also mentally mature, morally upright, and possess a strong work ethic, enabling them to compete in the global workforce.